Index of cardiac-electrophysiological balance and the effects of thrombolytic therapy on the electrocardiogram of patients with pulmonary embolism - Alsancak,Yakup (2020)
SUMMARY OBJECTIVE: Different parameters on electrocardiograms (ECG) have been investigated to predict arrhythmia and mortality in patients with acute pulmonary embolism (APE). The acute effect of thrombolytic therapy (TT) on these parameters has not been investigated yet. METHODS: We examined the data of 83 patients who were evaluated as high-risk APE and discharged from the hospital after TT. First, the high-risk APE patients’ ECGs were compared with healthy control subjects (n = 55). After their admission and 24 hours later, the ECGs of patients with APE were compared. Heart rate, P-wave morphology, QRS duration, QT distance, Tp-e, and the index of cardiac electrophysiological balance (iCEB) were analyzed. RESULTS: Although P maximum was not different between the groups’ ECGs, heart rate, QT, QTc (corrected QT) interval, Tp-e intervals, Tp-e/QT ratio, and P wave dispersion were significantly higher in the APE group ( P values < 0.031). iCEB or iCEBc (corrected iCEB) values were lower in APE group ( P < 0.001). After TT, we determined a decrease in heart rate, Tp-e interval, and Tp-e/QT ratio ( P < 0.001). Although we detected a decrease in the QT and QTc interval and QT dispersion (QTd), QTd had no statistical significance (respectively P -value 0.013, 0.029, and 0.096). The iCEB and iCEBc levels were lower after TT ( P -value was 0.035 and 0.044 respectively). CONCLUSION: The QT, QTc, Tp-e interval, Tp-e/QTc ratio, iCEB, and iCEBc values significantly decreased after TT. It may be thought that effective TT causes partial improvement in ventricular repolarization in an early period.